2001
DOI: 10.4049/jimmunol.167.11.6552
|View full text |Cite
|
Sign up to set email alerts
|

Role of p38 Mitogen-Activated Protein Kinase in Chemokine-Induced Emigration and Chemotaxis In Vivo

Abstract: It has been proposed that L-selectin engagement with ligand activates p38 mitogen-activated protein kinase (MAPK) and can impact on downstream events of leukocyte rolling, including adhesion, and emigration. Using a novel chemotactic assay in vivo, we visualized slow release of chemokine from an agarose gel positioned 350 μm from a postcapillary venule, which induced directed migration (chemotaxis) of neutrophils. In this system, keratinocyte-derived cytokine induced phosphorylation of p38 MAPK, which phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
102
4

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(114 citation statements)
references
References 36 publications
8
102
4
Order By: Relevance
“…This points to a general inhibition of synovial inflammation by p38 MAPK blockade rather than specific effects on single cell types, and suggests that p38 MAPK activation is a critical factor in the severity of synovial inflammation. It is compatible with our previous finding of overexpression of p38 MAPK in endothelial cells, allowing us to speculate that p38 MAPK blockade may affect transendothelial migration (27). Furthermore, the observed reduction in the expression of downstream cytokines such as IL-1 and RANKL is also in accordance with the reduction in the inflammatory response.…”
Section: Discussionsupporting
confidence: 91%
“…This points to a general inhibition of synovial inflammation by p38 MAPK blockade rather than specific effects on single cell types, and suggests that p38 MAPK activation is a critical factor in the severity of synovial inflammation. It is compatible with our previous finding of overexpression of p38 MAPK in endothelial cells, allowing us to speculate that p38 MAPK blockade may affect transendothelial migration (27). Furthermore, the observed reduction in the expression of downstream cytokines such as IL-1 and RANKL is also in accordance with the reduction in the inflammatory response.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, several reports have shown that SAPK2/p38 is involved in chemokine-induced chemotaxis of cells (16,34,70,71). Our study also presents evidence that SAPK2/p38 and SAPK1/JNK1, but not ERKs, intervene in the control of MCP-1-induced MonoMac6 migration.…”
Section: Discussionsupporting
confidence: 68%
“…These Rho-like G-proteins are known principally for their pivotal role in regulating the actin cytoskeleton in cell migration (Burridge and Wennerberg, 2004). PI3K has been thought to be a key molecule in the activation of cell migration through Rac signaling (Chandrasekar et al, 2003;van Leeuwen et al, 2003 Kawauchi et al, 2003) and p38MAPK (Rousseau et al, 1997;Cara et al, 2001;Ishizuka et al, 2001;Kimura et al, 2003;Pichon et al, 2004), have also been reported to be involved in cell migration. Consistent with these reports, our results indicate that activation of PI3K is required for the induction of glioma cell migration as well as for the activation of p38MAPK and JNK in response to LPA.…”
Section: Discussionmentioning
confidence: 99%